The influence of personality on dispersal and population dynamics in a passerine bird - Aguillon, Stepfanie Maria (The University of Arizona., 2014)
Dispersal influences the genetic and social composition of populations, yet it has been difficult to understand the mechanisms underlying dispersal and this limits our ability to understand how dispersal may be influencing population dynamics. Behavioral traits, such as aggression, have been implicated as drivers of both dispersal and population dynamics. However, the influence on both has never been addressed in a single system. Western bluebirds (Sialia mexicana) provide an excellent opportunity to address this question, as their dispersal propensity is dependent upon aggressive phenotype and we have detailed observations over a period of more than a decade. I show that natal dispersal is influenced by an interaction between father and son aggressive phenotypes, in addition to available resources on the natal territory. Furthermore, population density is influenced by resource availability and an interaction between population aggression and recruitment of offspring as breeders. Males that breed for multiple seasons once the population has reached saturation recruit a higher proportion of offspring into the population, as do males that are nonaggressive. Males that are nonaggressive are more likely to breed for multiple seasons, which suggests an added cost to aggressive behavior in this species. Both aggressive behavior and the availability of resources are mechanisms influencing dispersal of individuals that manifest at the population scale.